Autoimmune Disease: Budget-buster or Enlightened Solutions? - Beecham, James E; Seneff, Stephanie (Archives of Community Medicine and Public Health, 2017)
A rising epidemic among Americans threatens to disrupt the new US administration’s promise of affordable health insurance for all. The epidemic consists of a dramatic and ongoing increase in the incidence of autoimmune diseases (AD) across the populations of nearly all Western countries, diagnosed under approximately 100 different disease labels, and currently estimated to afflict up to 50 million Americans. One potential reason for the epidemic appears to be autoimmune reactions in people to immune ‘triggers’ in foods, a prime example of which may be the newly described GMO foods’ antigenic glyphosate-induced misfolded proteins. An analysis was undertaken, using a case study approach, to compare the relative cost/benefit ratios of treating the oncoming AD epidemic among Americans using the standard medicine (SM) pharmaceutical immunosuppression drug treatment model as compared to treating AD using a functional medicine (FM) approach of probiotics, lifestyle modification and improved diet choices along with governmental regulations to reduce consumption of trigger foods. We conclude that, for the American people over the next 10 years, applying only SM could cost up to 2 trillion more than a potentially equally or more effective diagnosis and treatment program emphasizing FM and government action to reduce trigger food consumption and avoid confounding influences from industry. While these two models are not mutually exclusive, our analysis suggests that the US government has a series of difficult choices ahead which will impact both its population’s health and the affordability of their health insurance over the next decade and beyond.